Chapter 3 - Threshold - J-A. van den Berg (Acta Theologica)
From text: From an architectonic perspective, a threshold facilitates an important transition. Norberg-Schulz (2000:144) defines a threshold as “that which we cross”, and as “a separatory transition”. The threshold, as a metaphor of liminality – denoting “a highly creative phase or space, where the combination of new forms and relations is possible” (Cilliers 2009b:169) – comprises part of the development of the space for the interdisciplinary dialogue, and is located at the centre thereof.